NLRP3 Inflammasome-Mediated Pyroptosis in Diabetic Nephropathy: Pathogenic Mechanisms and Therapeutic Targets - Chen Y; Chen R; Ji X; Zeng Z; Guan C (Journal of Inflammation Research, 2025)
Yichao Chen,1 Riqiu Chen,2 Xiaozhen Ji,2 Zhifu Zeng,2 Changrong Guan2 1School of Medicine, Hangzhou Normal University, Hangzhou, Zhejiang, 310000, People’s Republic of China; 2Department of Endocrinology, The Lishui Hospital of Wenzhou Medical University, The First Affiliated Hospital of Lishui University, Lishui People’s Hospital, Lishui, Zhejiang, 323000, People’s Republic of ChinaCorrespondence: Changrong Guan, Department of Endocrinology, The Lishui Hospital of Wenzhou Medical University, The First Affiliated Hospital of Lishui University, Lishui People’s Hospital, Lishui, Zhejiang, 323000, People’s Republic of China, Tel +86-18957097205, Email 76827579@qq.comAbstract: Diabetic nephropathy (DN) is a prevalent microangiopathic manifestation of diabetes mellitus (DM) and a pathological sequela of chronic glycemic disorders, characterized by several pathological features including glomerulosclerosis, podocyte loss, tubular epithelial atrophy and abnormal extracellular matrix accumulation. A growing body of research has underscored that chronic inflammatory microenvironments play a central role in the progression of DN. Pyroptosis, a newly defined form of programmed inflammatory necrosis, operates through the following molecular mechanism: inflammasome activation, gasdermin D (GSDMD)-mediated plasma membrane perforation and pro-inflammatory mediator release. Pyroptosis is triggered by the activation of the NOD-like receptor 3 (NLRP3) inflammasome. Classical (caspase-1) or non-classical (caspase-4/5/11) pathways activate pyroptosis by cleaving GSDMD, inducing enzymatic fragmentation of the GSDMD protein. GSDMD-N-terminal domain oligomerizes to form transmembrane pores, which further disrupt cellular osmotic homeostasis as well as membrane integrity. Inflammatory cascades are triggered when IL-1 and IL-18 are released as a result of subsequent cell lysis. This review systematically elucidates the pathobiological interplay between pyroptosis regulatory networks and the pathogenesis of DN and summarizes potential therapeutic compounds that mitigate pyroptosis by inhibiting NLRP3 inflammasome activation or blocking GSDMD pore formation. Preclinical studies suggest that targeting pyroptosis-related signaling molecules including NLRP3, caspase-1 and GSDMD may alleviate renal injury by suppressing inflammation-driven fibrosis and ameliorating glomerular dysfunction. Current studies emphasize that regulating pyroptosis mechanisms could slow DN progression, providing novel insights into the development of nephroprotective strategies.Keywords: diabetic nephropathy, inflammation, pyroptosis, NLRP3, Caspase-1/4/5/11, GSDMD, IL-1β and IL-18